2023
DOI: 10.3390/foods12112251
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Synbiotics on Dextran-Sodium-Sulfate-Induced Acute Colitis: The Impact of Chitosan Oligosaccharides on Endogenous/Exogenous Lactiplantibacillus plantarum

Abstract: In this work, Lactiplantibacillus plantarum (L. plantarum) isolated from mice feces (LP-M) and pickles (LP-P) were chosen as the endogenous and exogenous L. plantarum, respectively, which were separately combined with chitosan oligosaccharides (COS) to be synbiotics. The anti-inflammatory activity of LP-M, LP-P, COS, and the synbiotics was explored using dextran-sodium-sulfate (DSS)-induced acute colitis mice, as well as by comparing the synergistic effects of COS with LP-M or LP-P. The results revealed that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…50 In addition, SCFAs further assisted in enhancing the intestinal barrier function and maintaining the balance of the intestinal microbiota. 51,52 Numerous studies have shown that the short-chain fatty acid content is decreasing in DSS-induced colitis mice. 28,53 This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…50 In addition, SCFAs further assisted in enhancing the intestinal barrier function and maintaining the balance of the intestinal microbiota. 51,52 Numerous studies have shown that the short-chain fatty acid content is decreasing in DSS-induced colitis mice. 28,53 This is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 The HS intervention group showed an increase in the relative abundance of Dubosiella, which is consistent with the effect of prebiotics on DSS-induced acute colitis. 39 Dubosiella, an anaerobic Gram-positive bacterial genus, is believed to possess multifaceted benefits, such as regulating metabolism, enhancing intestinal immune function, and resisting inflammatory diseases. 40 Furthermore, similarities observed in the gut microbiota between the control group and the HS group imply that SL may enhance intestinal health by modulating the structure of the gut microbiota and constraining the activity of pathogenic bacteria in the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…It has been intrinsically linked to metabolic diseases such as type 2 diabetes mellitus, obesity, and inflammatory bowel disease [ 11 , 12 , 13 ]. Therefore, maintaining a favorable equilibrium in the gut microbiome is beneficial for host health [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%